Pengendalian Kualitas Part Trim Rear Quarter Right APV Arena dengan Menggunakan Metode Six Sigma di PT. Suzuki Indomobil Motor - Fatimah Zahara (Jurnal Optimasi Sistem Industri, 2014)
Quality is an important aspect in enhancing the competitiveness of the product. Quality's role is to give satisfaction to the customer and be able to compete with similar products. During of the production process there is a chance that the products are not produced in established standards. Products that not suitable with the specifications is a defect that would cause harm to the company. Trim Rear Quarter Right is a component of the APV Arena car which is each production of Trim Rear Quarter Right there are at least one or more defective products. This of course would lead to losses for the company. The method used in this case study is the six sigma method because this method has been proven effective. Defect in Trim Rear Quarter Right caused by five factors that is negligence of the operator in set up the machine, the age of the machine , the quality of the materials, the application of the method is not maximized and noisy environments. The set up process of injection molding machine is the most influential in causing the defect product with RPN (Risk Priority Number) value is 256.